2011
DOI: 10.1021/bc200173e
|View full text |Cite
|
Sign up to set email alerts
|

Novel Anticancer Polymeric Conjugates of Activated Nucleoside Analogues

Abstract: Inherent or therapy-induced drug resistance is a major clinical setback in cancer treatment. The extensive usage of cytotoxic nucleobases and nucleoside analogs in chemotherapy also results in the development of specific mechanisms of drug resistance; such as nucleoside transport or activation deficiencies. These drugs are prodrugs; and being converted into the active mono-, di- and triphosphates inside cancer cells following administration, they affect nucleic acid synthesis, nucleotide metabolism, or sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 40 publications
(54 reference statements)
3
48
0
Order By: Relevance
“…For example, we recently developed nanogel-nucleoside analog conjugates with polyphosphate linker that was stable even after oral administration. 34 NRTI prodrugs based on cationic ε -polylysine are inexpensive and can be obtained using simple synthetic procedures. We also anticipate potential application of PEG-CEPL-sNRTI nanodrugs for more efficient therapy of HIV-1 infection in the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we recently developed nanogel-nucleoside analog conjugates with polyphosphate linker that was stable even after oral administration. 34 NRTI prodrugs based on cationic ε -polylysine are inexpensive and can be obtained using simple synthetic procedures. We also anticipate potential application of PEG-CEPL-sNRTI nanodrugs for more efficient therapy of HIV-1 infection in the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Floxuridine conjugates of peptides have been synthesized to target peptide transporter 1 (PEPT1, SLC15A1 ) with the objective of increasing oral bioavailability, lowering variability in uptake, and preventing conversion to 5-FU by TP (10, 11). Additionally, polymer conjugates of its active triphosphate form have been synthesized (12), as well as phosphoactivated (13), phosphoramidated (14), and alkyl ester (15, 16) forms of floxuridine prodrugs. These prodrugs aim to enhance floxuridine bioavailability and to promote its tumor-specific delivery, thus reducing non-specific toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that nanogel-drug conjugates (nanodrugs) of floxuridine and gemcitabine are efficient against regular and drug-resistant tumors (11, 12). The nanodrugs containing nucleoside analogs attached via the tetraphosphate linker to CPVA demonstrated strong tumor growth inhibition activity even against drug-resistant cancers.…”
Section: Introductionmentioning
confidence: 99%